You just need to move things from one side of the equation to the other. I would start by adding 7x to both sides of the question, which results in:
4 = 1 + x
I would then subtract one from both sides, which results in:
3 = x
As such, x = 3, which is the answer.
2006-10-01 13:52:16
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
x = 3
2006-10-01 21:03:35
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
x=3
2006-10-01 20:57:33
·
answer #3
·
answered by whattheheck 4
·
1⤊
0⤋
The first and third person are correct. Why?
4-7x=1-6x (as the second person said, move the integers to one side and the whole numbers to the other)
6x-7x=1-4
-1x=-3 (divide both sides by -1)
x=3
2006-10-01 20:55:17
·
answer #4
·
answered by morningstar 3
·
1⤊
0⤋
x = 3
2006-10-01 20:52:40
·
answer #5
·
answered by KYP 1
·
1⤊
0⤋
4 - 7x = 1 - 6x (Add 6x to both sides and subtract 4 from both sides)
-x = -3 (Divide both sides by -1)
x = 3
Check:
4 - 7(3) = 1 - 6(3)
4 - 21 = 1 - 18
-17 = -17
QED
2006-10-02 12:12:39
·
answer #6
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
4-7x=1-6x add 7x to both sides
4=1+x solve for x
x=3
2006-10-01 20:51:46
·
answer #7
·
answered by Rckets 7
·
1⤊
0⤋
x=3.
2006-10-01 20:51:24
·
answer #8
·
answered by zee_prime 6
·
1⤊
0⤋
Get the x's on one side of the equation and the integers on the other side to solve.
Step 1: Add 6x to each side, to get:
4 - x = 1
Step 2: Subtract 4 from each side, to get:
-x = -3
Step 3: Multiply both sides by -1, to get:
x = 3
2006-10-01 20:51:15
·
answer #9
·
answered by I ♥ AUG 6
·
1⤊
0⤋
4-7x = 1-6x
-4 +6x
-x =-3
/-1 /-1
x = 3
sry its not lining up....
2006-10-01 20:54:52
·
answer #10
·
answered by Storm G. 2
·
1⤊
0⤋